Liquidity Risk Management and Financial Performance of Commercial Banks: a Case of Absa Bank-Masindi - Milly Harriet Mukula (Uganda Christian University, 2024)
The financial performance of commercial banks has been averagely low in the past years. This was due to improper risk management strategies on different kind of financial risks that faced commercial banks in Uganda. This causes the liquidation of some commercial banks (Crane bank). This main study sought to find the effect of financial risk management on the financial performance of commercial banks in Uganda. The specific objectives were to assess the effect of credit risk, interest rate risk, and exchange rate risk on financial performance of the banks. The target population of the study was 40 and the sample size 36 respondents using the Slovene’s formula composed by managers and executives. The study used a case study research design. The simple linear regression and multiple regression analysis were used to analyze data. The main instrument was questionnaire and key informant interview. Thus, the regression analysis showed that financial risk management affects financial performance of commercial banks in Uganda. Specifically credit risk was regressed with financial performance, the result of the linear regression showed F-statistic 274.652 at P<.05 ;interest rate risk was regressed with financial performance, the result of the linear regression showed F-statistic 315.259 at P<.05; exchange rate risk was regressed with financial performance, the result of the linear regression showed F-statistic 250.823 at P<.05; this means that both credit, interest rate and exchange rate risk have significant effect on financial performance. The results of multiple regression analysis performed simultaneously on the variables showed that financial risk management has a positive strong effect on financial performance, this means that effective financial risk management will lead to a healthy financial performance of Stanbic bank in Uganda. The study concluded that credit risk, interest rate risk and exchange rate risk had statistically significant effect on banks financial performance in Uganda for the period under study and this explains 88.3 percent on the financial performance. The study recommended that given the current supervisory and regulatory policy frameworks for banks, risk managers should be more concerned with managing risk coming from financial operations and that future studies in this area be carried out for longer study periods and more independent variables, in order to bring out the true picture of the effect of financial risk management on financial performance. This study advanced knowledge by linking the escalating financial performance of commercial banks in Uganda to disregard of stakeholder theory.